Presentation - González-Becerril, Juan Gabino (Papeles de Población; Vol. 23 Núm. 94 (2017): Papeles de Población, 2017)
Upon concluding the search and rescue activities in the buildings collapsed in the September 19th earthquakes, the Federal government disclosed that up to October 4th, 369 deceases caused by the earthquake had been recorded. Of this figure, 228 deceases occurred in Mexico City, 73 in Morelos, 45 in Puebla, 15 in the State of Mexico, six in Guerrero and one in Oaxaca.1 Among the figures, there appear questions about why the government was surpassed by civil society in responding and act to remove the remains and save lives in Mexico City. Why only the millennials were the only ones that stood up for Mexico City? How many died in the earthquake? How many lost a parent? How many parents lost a child? How many buildings and houses fell down? How many resources is needed to rebuild Mexico City and other states that suffered damage from the earthquake? Where have domestic and international private and governmental donations gone? Why more women died in S19?2 What next, how to start, who turn to, and where to start a new life? Will there be a massive moving from Mexico City to the State of Mexico or other states? But, what occurred and when are the adjoining states going to receive support? Or for Oaxaca, Guerrero and Chiapas, where there are many earthquakes?